Methodological basis for the conversion of transport diesel engines of transport diesel engines to gas-diesel operation - Glazyrin, С.А.; Varlamov, Г.Б.; Barabash, П.А.; Petrenko, В.Г.; Bimurzina, З.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The expediency of the search, development and use of alternative environmentally friendly motor fuels is scientifically substantiated, the main of which is the use of gas fuel, which is much more efficient than diesel fuel in terms of overall environmental safety. The relevance of the research carried out and the developments proposed in this article will make it possible to realize the fundamental complex advantages of the ecological and operational nature of the use of the gas-diesel cycle of the ICE operation. This is in line with the Paris Protocol on a climate to reduce greenhouse gas emissions to keep the global average temperature rising. The paper describes the main features and methods of converting diesel engines to theircompressed natural gas power supply. The advantages and disadvantages of all methods of implementing the gas-diesel cycle on existing diesel installations of low and high power are analyzed in detail. The main operations and changes in operating parameters for each method of implementing the gas-diesel cycle on operating diesel engines are also described. The use of a mixed quantitative and qualitative control of the supply of compressed gas and diesel fuel for various loads of a diesel engine operating on a gas-diesel cycle has been scientifically substantiated. The systematization is carried out and the comparative characteristics of liquid and gas motor fuels, which can be used for the implementation of the gas-diesel cycle in diesel engines, are presented in tabular form, general conclusions are described.